Identification of a Novel COL4A4 Variant in Compound-Heterozygous State in a Patient With Alport Syndrome and Histological Findings Similar to Focal Segmental Glomerulosclerosis (FSGS) - Zhu, Feng; Li, Wencheng; Li, Zhenqiong; Zhu, Hongyan; Xiong, Jing (Frontiers in Genetics, 2019)
Abstract Alport syndrome (AS) is a rare and inherited renal disorder with an autosomal recessive mode of inheritance. AS patients usually manifested with hematuria and progressive renal disorder but also occasionally accompanied with hearing loss and ophthalmic disease. Germline variants in collagen type IV α-4 (COL4A4) gene lead to autosomal recessive Alport syndrome. In the present study, we investigated a Chinese family with Alport syndrome. The index patient is a 24-year-old Chinese woman who has been suffering from proteinuria. Renal biopsy and renal pathology were performed and found focal segmental glomerulosclerosis (FSGS) like lesion in this index patient. The index patient was also presented with binocular edema and blurred vision. However, binocular edema was dissipated gradually without any further treatment. Unlikely, the index patient was not identified with hearing impairment. Index patient’s parents are phenotypically normal. Targeted next generation sequencing and Sanger sequencing was performed. A novel heterozygous single nucleotide insertion, c.4760_4761insC and a previously reported likely pathogenic variant, c.1323_1340delTGGCTTGCCTGGAGCACC in the COL4A4 gene was identified in the index patient. The novel heterozygous single nucleotide insertion (c.4760_4761insC) leads to a frameshift which finally results in the formations of a truncated COL4A4 protein. In addition, the other heterozygous likely pathogenic variant; c.1323_1340delTGGCTTGCCTGGAGCACC has been already reported for causing AS with an autosomal recessive mode of inheritance. Sanger sequencing confirmed that these two variants were inherited in the index patient from her father and mother respectively. These two variants are not found in 100 normal control individuals. In conclusion, our present finding emphasizes the significance of high throughput targeted next generation sequencing technology for rapid and cost-effective genetic screening which allow us easy and accurate clinical diagnosis of AS patients.